Kajian Ulum al-Qur’an dalam Pandangan Mufassir Nusantara Tgk. Hasbie Asshidiqie - Agung Perdana Kusuma (Qur'an and Hadith Academic Society, 2017)
In this paper, it contains the opinion of the mufassir nusantara in using the ulum al-Qur'an method applied to the commentary. Hasbie Ash-Siddiqie in his An-Nur commentary also uses the ulum al-Qur'an method. Not all the methods in ulum al-Qur'an are explained in this paper. Only a few examples of this method, the view of Hasbi Ash-Siddiqie applies in his commentary. The method used in this paper is a description-analysis that describes the problem associated with obtaining a comprehensive understanding. It starts with reading the life history of Hasbi Ash-Siddiqie. Then the background of the commentator in writing the commentary. After that, the speaker will analyze through ulum al-Qur'an from Hasbi Ash-Siddiqie. The data collection technique used in this research is literature study (Library Research). Then the data is analyzed qualitatively.